Job performance among non-executive employees at Universiti Teknikal Malaysia Melaka / Nur E’ezati Md Sofri - Md Sofri, Nur E’ezati (2014)
The title of this research is “Job Performance of Non-Executive Employees at Universiti Teknikal Malaysia Melaka, UTeM”. The first purpose of this research is to examine the level of job performance among non-executive employees in more detail especially at Chancellery, UTeM. The second purpose is to determine the significant relationship between job dimension and job performance. There are five independent variables involved in this research which are Skill Variety, Task Identity, Task Significant, Autonomy and Feedback. In order to completing this research, the hypothesis was been constructed and focused on the objective to determine whether there has significant relationship between those independent variables with Job Performance. A total of 120 employees have participated in this study as respondents. The methodology used for the research was primary data collection. For primary data, the researcher was used the method of questionnaire to obtained and collect the information. Thus, the result was been obtained through the analyzing and interpret data of result. The reliability test, frequency analysis, descriptive testing, Pearson’s correlation coefficient testing and regression method was used for data analysis. From the correlation testing, the result shows four independent variables have a moderate relationship with Job Performance while Autonomy is shows inverse result which is low relationship. For multiple regression analysis testing, the result indicates that from five independent variables there are three variables which is Skill Variety, Task Identity and Task Significance have proven that they are the factor in influenced Job Performance compared to Autonomy and Feedback which clearly shows that both independent have contributed weak factor in influencing Job Performance. For hypothesis, there are clearly shown that three of hypothesis which including Skill Variety, Task Identity and Task Significance is supported while the other two Autonomy and Feedback is not supported.